PENERAPAN SISTEM BUDIDAYA IKAN BERKELANJUTAN DENGAN KONSEP NATURAL PADA RESTORASI LINGKUNGAN, SOSIAL DAN PEREKONOMIAN KAMPUNG NELAYAN KAMAL MUARA - Wilianto, Juan Nathanie; Sutanto, Agustinus (Jurusan Arsitektur dan Perencanaan, 2024)
Kampung Nelayan Kamal Muara, once a vibrant coastal community, is now ensnared in environmental and social degradation. Marine pollution, reclamation, and excessive exploitation of natural resources have triggered the death of marine life, habitat destruction, silting, and changes in ocean currents. This has not only taken away livelihoods and economies but also a sense of security, connection to the environment, cultural identity, and has the potential to turn Kamal Muara into a